Rumos da pintura na era da imagem técnica - Alan Fontes Borges (2010)
To study upon the presence of painting in contemporary art in the period between the years 2000 until today. This survey intend to produce a wide iconographical research intending to establish characteristics and issues of language present in painting after surpassing its previous century paradigms.It is both a critical-theoric and plastic exercise resulting from the research in painting called A Casa. That research, which was initiated in 2004, promotes a reflection on the amplification of the painting field, such in the aspect of the bidimentional support as of its relation with other media, regarding the expansion of the observers perception.